SAMPLE SIZE AND SAMPLING IN QUALITATIVE RESEARCH - อินทพรหม, วัชรินทร์ (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2019)
This article aims to present method of finding sample size or number of samples and sampling method or selection of key informants from population of qualitative research. According to relevant literature review, it is observed that size or number of samples depends on two requirements; (1) requirement for small samples can be determined by saturation or data redundancy, which summarize required number of samples size, and (2) requirement for large sample to demonstrate variation within target group, which needs large sample sizes to assess variety or patterns, expressed by target population, that are appropriate and interesting. Size or number of samples depend on research purpose and data collection method. Principles of projection or rule of thumb may apply such as social phenomena study with approximately 10 people for sample size (if data is sufficiency and saturated or redundant, sample size may be smaller). In-depth interview, approximately 30 people for sample size, group discussion with average 5-10 people per group, etc. Method of sampling or selection of key informants for qualitative research is conducted based on sample appropriateness principle as well as unique and diverse methods such as intensive sample selection, specific sample selection, sample selection based on specific criteria, which are unique samples related to research questions. Randomized or selected samples can provide reliable and adequate data for analysis to answer research questions.